2020
DOI: 10.1155/2020/2890536
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of a Novel High Phenolic Sorghum Bran in Human Colon Cancer Cells

Abstract: Human colon cancer is the third leading cause of mortality in the United States and worldwide. Chemoprevention using diet is widely accepted as a promising approach for cancer management. Numerous population studies indicate a negative correlation between the incidence of colon cancer and consumption of whole grains with a high content of bioactive phenolic compounds. In the current study, we evaluated the anticancer properties of a high phenolic sorghum bran extract prepared using 70% ethanol with 5% citric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Previous studies have shown a wide range of potential biological activities of sorghum 3-deoxyanthocyanidins, including anti-proliferative and pro-apoptotic effects against colon cancer cells [ 9 ] and reducing oxidative stress via increasing the NADH:quinone oxyreductase (NQO) ratio [ 10 ]. Smolensky et al demonstrated the versatile biological roles of phenolic extracts of PI570481, a novel high polyphenol sorghum type, including anti-cancer and anti-microbial effects [ 11 , 12 , 13 , 14 ]. In addition to their powerful antioxidant ability [ 15 ], sorghum-condensed tannins have shown great inhibitory activities against digestive enzymes, which may partially contribute to the anti-diabetic capacity of sorghum [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a wide range of potential biological activities of sorghum 3-deoxyanthocyanidins, including anti-proliferative and pro-apoptotic effects against colon cancer cells [ 9 ] and reducing oxidative stress via increasing the NADH:quinone oxyreductase (NQO) ratio [ 10 ]. Smolensky et al demonstrated the versatile biological roles of phenolic extracts of PI570481, a novel high polyphenol sorghum type, including anti-cancer and anti-microbial effects [ 11 , 12 , 13 , 14 ]. In addition to their powerful antioxidant ability [ 15 ], sorghum-condensed tannins have shown great inhibitory activities against digestive enzymes, which may partially contribute to the anti-diabetic capacity of sorghum [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…found that treatment of breast cancer with Hwanggeumchal sorghum blocked its metastasis to the lungs and modulated the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway. In addition, high phenolic sorghum extract (accession PI570481) reduced cancer cell migration and invasion with downregulation of β ‐catenin and VEGF 58 . These findings suggest a potential use of sorghum components for the management of late‐stage cancer.…”
Section: Health‐beneficial Effects Of Sorghummentioning
confidence: 87%
“…Several bioactive compounds in sorghum extracts inhibit the anti‐apoptotic protein BCL‐2 in breast cancer cells, 44, 56 and in leukemia cells, 57 and up‐regulate pro‐apoptotic proteins (such as BAK and BAX) and cleavage of caspase 9, caspase 3, PARP, and lamin B in HL60 leukemia cells 57 . Recently Lee et al 58 . observed that a novel high phenolic sorghum (accession PI570481) originally from Sudan showed pro‐apoptotic activity in human colorectal cancer cells (HCT15, SW480, HCT116, and HT‐29) with increased cleavage of caspase‐3 and PARP.…”
Section: Health‐beneficial Effects Of Sorghummentioning
confidence: 99%
See 2 more Smart Citations